Mengenalkan Bahasa Arab Melalui Media Lagu Pada Siswa Tapos Sekartaji Ketawang - Nurul Fitria Aprilia (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to describe the utilization of song media in Arabic language learning and its impact on students' interest and understanding at Tapos Sekartaji, Ketawang. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that song media can increase learning enthusiasm, facilitate vocabulary mastery, improve pronunciation, and create a pleasant learning atmosphere. Students become more active and confident in using Arabic. Although there are obstacles such as limited references to suitable songs, teachers are able to overcome them with creativity in composing lyrics that are relevant to the teaching material. Thus, song media is an effective and innovative learning strategy in introducing Arabic to students.